PMA Muadalah sebagai Tantangan dan Peluang Meningkatkan Standar Pendidikan Pesantren - Siti Aimah (IAI Darussalam, 2020)
Education in pesantren, in general, from time to time is almost unchanged. The concept of “al-Muhaafadhatu ala 'al-qadiimi as-shaalih wa al-jahdu bi al-Jadiidi al-ashlah” implies pesantren through consistently maintaining the spirit of pesantren by providing education oriented to